Poczucie szans życiowych i jego związki z motywacją na przykładzie studentów szkoły wyższej niepublicznej = Sense of life chances and its connections with motivation - an example of students of a private university - Chyła, Marta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article describes the mechanics that can influence social (especially professional) mobility of graduates of private universities and the school`s position. It is about the connection of students` sense of social chances with their motivation to act. Contemporary theories of motivation recognize the human being as an active person, not a passive object of influences.
Keywords: szkolnictwo wyższe; studenci; aspiracje życiowe